PEMBERDAYAAN KELOMPOK TANI SAYUR di KELURAHAN KAKASKASEN II KECAMATAN TOMOHON UTARA KOTA TOMOHON - KURES, NAFISY NEVARIA INDONASA; PANGKEY, MASJE SILIJA; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract : Empowerment is etymologically derived from the word "power" which means strength or ability. So empowermentcan be interpreted as a process toward empowerment, or process to get power / ability / ability, and or process of power / power/ ability from party that have power to party which less or not helpless Sulistiyani (2004: 77). Empowerment of farmer groups isa model of empowerment that the direction of development favours the people. Farmer groups are basically the main actors ofrural development. This research uses descriptive method of qualitative approach. This study describes the data obtained fromthe results of research on the Empowerment of Vegetable Farmers Group in Kakaskasen II Subdistrict Tomohon DistrictTomohon North. In qualitative research, data collection is done by observation, in-depth interview and documentation. Basedon the results of the study concluded that the empowerment of vegetable farmer groups seen from three indicators categorizedis good enough. Seen from the development (enabling) vegetable farming groups are quite good, seen from farmers who havebeen able to develop their farm business. In strengthening the potential or power (empowering) vegetable farming groups havebeen good, because the farmers have been able to increase the potential or power that is owned by directly practice in the fieldand are willing to accept new things in the field of agriculture. For the independence of the vegetable farmer group is goodenough, because there have been efforts from farmer groups to establish a farmer group that they run. In order for assistanceprograms from the Agriculture Agency to the vegetable farming group in Kakaskasen II to run well, this issue becomes animportant note for the Government through the Agriculture Office to provide the targeted assistance and socialization in theavailability of such assistance. In Developing and Strengthening Potential or Power For the members of farmer groups andfarmer groups, the group of farmers should be upgraded to be able to develop farmer groups in a positive and competitive wayin the agricultural world. In strengthening the potential or power, so that farmer groups can change the mind-set in applyingthe existing technology and improve the human resources of farmers to be able farmers to be able to adapt to technologicalprogressKeywords: Empowerment of Vegetable Farmer Group